Antheridial development in the moss Physcomitrella patens: implications for understanding stem cells in mosses. (5th February 2018) - Kofuji, Rumiko; Yagita, Yasushi; Murata, Takashi; Hasebe, Mitsuyasu
Abstract : Stem cells self-renew and produce precursor cells that differentiate to become specialized cell types. Land plants generate several types of stem cells that give rise to most organs of the plant body and whose characters determine the body organization. The moss Physcomitrella patens forms eight types of stem cells throughout its life cycle. Under gametangium-inducing conditions, multiple antheridium apical stem cells are formed at the tip of the gametophore and each antheridium apical stem cell divides to form an antheridium. We found that the gametophore apical stem cell, which typically forms leaf and stem tissues, changes to become a new type of stem cell, which we term the antheridium initial stem cell. This antheridium initial stem cell produces multiple antheridium apical stem cells, resulting in a cluster of antheridia at the tip of gametophore. This is the first report of a land plant stem cell directly producing another type of stem cell during normal development. Notably, the antheridium apical stem cells are distally produced from the antheridium initial stem cell, similar to the root cap stem cells of vascular plants, suggesting the use of similar molecular mechanisms and a possible evolutionary relationship. This article is part of a discussion meeting issue 'The Rhynie cherts: our earliest terrestrial ecosystem revisited'.